2013
DOI: 10.1016/j.jval.2013.08.2293
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of PRO Label Claims Granted by the FDA as Compared to the EMA (2006–2010)

Abstract: The EMA is more likely than the FDA to grant PRO claims and for higher order constructs. On a macro level, there appears to be poor concordance between claims granted by both agencies. On close examination, however, there appears to be greater concordance than previously recognized, which may be instructive in formulating future PRO strategies. Further research to create strategic alignment across agencies may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 6 publications
1
48
0
Order By: Relevance
“…Additionally, 21.7% of orphan-designated approvals in the studied sample presented PRO claims in their SmPCs. This is significantly below the 47% reported PRO claims for all new drug approvals by the EMA from 2006 to 2010 [11] and the 46% reported from 2008 to 2012 [12]. Conversely to the above mentioned studies, which analysed the entire content of the European Public Assessment Reports (EPARs), we focused only on the SmPCs, because they include PRO claims granted by the EMA.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, 21.7% of orphan-designated approvals in the studied sample presented PRO claims in their SmPCs. This is significantly below the 47% reported PRO claims for all new drug approvals by the EMA from 2006 to 2010 [11] and the 46% reported from 2008 to 2012 [12]. Conversely to the above mentioned studies, which analysed the entire content of the European Public Assessment Reports (EPARs), we focused only on the SmPCs, because they include PRO claims granted by the EMA.…”
Section: Discussionmentioning
confidence: 96%
“…This can be partially explained by the fact that, while primary endpoints were typically based on disease symptoms, the FDA-approved PRO claims were symptom-based. Also, the EMA is more inclined to approve HRQoL and functioning measures, although not as primary endpoints [5,11]. All but one approval with a non-primary-endpoint-based PRO claims in our sample involved higher degree outcomes, such as HRQoL or functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, over the last decade or so, both the EMA and the FDA have shown increasing levels of interest towards PRO usage during MA procedures [20,24]. EMA appeared, however, to be more flexible and open to the inclusion of validated and clinically/methodologically appropriate PROs [33]. Indeed, many EMA disease-specific guidelines now require PRO endpoints to be included as secondary endpoints (e.g., the Ankylosing Spondylitis Quality of Life; ASHRQoL) [34].…”
Section: Discussionmentioning
confidence: 99%
“…proved product labels 2006-2010, identified that 24% were granted PRO claims [2], with a comparison of FDA and EMA labelling showing that the EMA is more likely than the FDA to approve PRO claims [3]. The majority of PRO data that is captured does not make it onto the regulatory approved label, this is particularly noted in oncology [4] which is currently being actively addressed by industry and regulators [5].…”
mentioning
confidence: 99%